Early Closure of a Temporary Ileostomy in Patients with Rectal Cancer - Mirwais, Maryam Munir, Shumaila Sikander, Rehman Shah, Imran Haider, Faisal Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Rectal cancer is a common malignancy affecting millions of individuals worldwide. Surgery is the primary treatment modality, and for many patients, the creation of a temporary ileostomy is required to protect the anastomosis and allow for healing. Objectives: The main objective of the study is to find the safety and feasibility of early ileostomy closure within four to eight weeks of the initial surgery compared to traditional closure time frames of six to twelve months and to examine the potential benefits of early ileostomy closure, including reductions in morbidity, improved quality of life, and decreased healthcare costs. Material and methods: This multicenter study was conducted in Surgical Department Lady Reading hospital Peshawar during 1st January 2020 to 30th June 2020. Data on patient demographics, medical history, surgical procedures, and postoperative outcomes were collected using medical records and standardized data collection forms. Patient-reported outcomes, such as quality of life and stoma-related complications, may also have been assessed using validated instruments. Results: Demographic data of the 60 patients included in the study showed a median age of 62 years (range: 42-84 years) and a male-to-female ratio of 1:1.3. The majority of patients (70%) had an American Society of Anesthesiologists (ASA) physical status of 2 or 3, indicating mild to moderate systemic disease. The median body mass index (BMI) was 25 kg/m² (range: 18-35 kg/m²), with 30% of patients classified as overweight (BMI 25-29.9 kg/m²) and 13% classified as obese (BMI ≥ 30 kg/m²). Practical implication: This article will helps to support the safety and efficacy of early closure of temporary ileostomy in patients with rectal cancer. Conclusion: In conclusion, this study provides evidence to support the safety and efficacy of early closure of temporary ileostomy in patients with rectal cancer. The results indicate that there were no significant differences in the incidence of complications between early closure and traditional closure groups. Keywords: Temporary, Ileostomy, Patients, Rectal, Cancer